(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article aims at publishing two paleo-hispanic stamps made over loom weights of the Samitier collection. They come from Durón de Belmonte and have been not collected in the Monumenta Linguarum Hispanicarum. The article also includes an analysis of the stamps made over Middle-Ebro valley ceramic productions in the Iberian-Roman period.